Cultural Self-identification in Terms of Bilingualism by Chingiz Aitmatov - Vaskiv, Mykola; Anisimova, Liudmyla (Journal of History Culture and Art Research, 2020)
The article deals with a phenomenon of bilingualism of Soviet national writers, who created their works both in mother-tongue and Russian language, and exceptionally in Russian. The brightest example of such kind of an artist is Kyrgyz classical writer of the second part of the 20th century Chingiz Aitmatov. The aim of our research was to define Chingiz Aitmatov’s cultural self-identification in a situation of bilingualism in his native Kyrgyzstan during Soviet times. The function of Russian language and culture for Chingiz Aitmatov’s creative works and author’s reflection concerning such issue as Russian culture as a mediator in familiarizing of small nations of the USSR with the world cultural heritage were also studied. Aitmatov considered the Russian language to be a “no compromise one” for USSR nations and small peoples in common Soviet informational space, particularly literary, in a process of integration to the global political, economic, and cultural heritage. At the same time, he put Russian culture in one cohort with the leading world cultures. According to Aitmatov, Russian cultural space had a great influence on the development of Soviet nations of Central Asia and became a mediator in a process of integration of small nations into the global cultural space. The Russian language was a helpful tool for acquaintance with the ancestry of world cultures.